2002
DOI: 10.1038/sj.ijo.0802070
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein apolipoprotein A-I kinetics in obese insulin resistant patients. An in vivo stable isotope study

Abstract: AIMS=HYPOTHESIS:Mechanisms responsible for the decreased high-density lipoprotein (HDL) cholesterol level associated with insulin resistance in obese patients are not clearly understood. To determine the influence of insulin resistance at an early stage on HDL metabolism, we performed a stable isotope kinetic study of apolipoprotein (apo) A-I, in five obese insulin resistant women with normal fasting triglycerides and without impaired glucose tolerance, and in five age-matched control women. METHODS: Each subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 31 publications
6
40
1
1
Order By: Relevance
“…Dyslipidemia has been reported as a risk factor for type 2 diabetes by several prospective studies High plasma triglycerides and low plasma HDL cholesterol levels are both seen in the insulin resistance syndrome, which is a prediabetic state suggesting that nonfasting triglycerides and HDL cholesterol levels reflect the degree of insulin resistance (Pont et al, 2002). Similarly the present study found that increased mean CBMN frequency (12.87) in subjects with H/o dyslipidemia.…”
supporting
confidence: 74%
“…Dyslipidemia has been reported as a risk factor for type 2 diabetes by several prospective studies High plasma triglycerides and low plasma HDL cholesterol levels are both seen in the insulin resistance syndrome, which is a prediabetic state suggesting that nonfasting triglycerides and HDL cholesterol levels reflect the degree of insulin resistance (Pont et al, 2002). Similarly the present study found that increased mean CBMN frequency (12.87) in subjects with H/o dyslipidemia.…”
supporting
confidence: 74%
“…These findings can be explained by increased cholesterol uptake from HDL by SR-BI scavenger receptors, which is known to be selectively greater from LpA-I:A-II particles (34), making them susceptible to degradation. The fractional catabolic rate for apoA-I is increased in cases with insulin resistance (35) but not so for apoA-II (36). However, apoA-II production is considered to be a determinant of LpA-I:A-II (37) but is not different in the insulin-resistant state (36).…”
Section: Discussionmentioning
confidence: 99%
“…A more controlled stable isotope kinetics study of apoA-I was performed in five obese, insulin-resistant women with normal fasting triglycerides without impaired glucose tolerance and in five age-matched control women in the postprandial state (46). In these obese individuals, apoA-I catabolism was increased markedly by 50% versus normal controls, resulting in a significant reduction in plasma apoA-I residence time.…”
Section: Hdl Kinetics Studies In Humans With Common Low Hdl-c Disordersmentioning
confidence: 99%
“…Furthermore, plasma HDL-C levels were significantly correlated with the apoA-I FCR and not with the apoA-I production rate. Thus, the authors concluded that accelerated apoA-I catabolism, and not production, is the main factor responsible for the decrease in HDL-C levels observed in obese, insulin-resistant subjects (46).…”
Section: Hdl Kinetics Studies In Humans With Common Low Hdl-c Disordersmentioning
confidence: 99%